The fabrication of TMJ 3D model for arthrocentesis and athroscopy simulation / Foo Qi Chao - Foo, Qi Chao (2019)
Background: Arthrocentesis and arthroscopy are relatively safe procedures for treatment of arthrogenic Temporomandibular Disorders (TMD). This study aims to fabricate a Temporomandibular joint (TMJ) 3D model for arthrocentesis and arthroscopy simulation. Material and Methods: Based on data collected from cadaveric dissection, a TMJ prototype was designed with 3D design software. Prototype was 3D printed and arthrocentesis and arthroscopy simulation trial were conducted on the model. Results: The prototype satisfied key parameters of having a palpable zygoma, watertight TMJ capsule, mouth opening of >35mm and detachable parts for replacement after simulation. In terms of surgical simulation, we were able to identify key anatomical structures such as the canthus and tragus for surgical marking, and successfully insufflate and irrigate the upper joint space of the TMJ to simulate arthrocentesis and arthroscopy lysis and lavage. The total printing cost for this prototype was RM 628 (USD 151.36) with the cost of replacement parts after simulation at RM 103 (USD 24.82). Conclusion: This TMJ prototype can be used for teaching and training of arthrocentesis and arthroscopy. Keywords: temporomandibular joint, athrocentesis, arthroscopy, simulation